Real-world Outcomes and Predictive Biomarkers for 177Lutetium Prostate-specific Membrane Antigen Ligand Treatment in Metastatic Castration-resistant Prostate Cancer: A European Association of Urology Young Academic Urologists Prostate Cancer Working Group Multi-institutional Observational Study - Kafka, Mona; Horninger, Andreas; di Santo, Gianpaolo; Virgolini, Irene; Neuwirt, Hannes; Unterrainer, Lena M; Kunte, Sophie C; Deiss, Emil; Paffenholz, Pia; Heidenreich, Axel; Rasul, Sazan; Einspieler, Holger; et al. (European urology oncology, 2024)
BACKGROUND: The European Association of Urology guidelines include the lutetium-177 (177Lu) PSMA-617 prostate-specific membrane antigen (PSMA) ligand as a therapy option for metastatic castration-resistant prostate cancer (mCRPC). A major challenge in clinical practice is to pursue a personalized treatment approach based on robust predictive biomarkers. OBJECTIVE: To assess the performance of 177Lu PSMA in real-world practice and to elaborate clinical biomarkers for evaluating treatment responses. DESIGN, SETTING, AND PARTICIPANTS: We conducted a retrospective observational study including 233 patients with mCRPC treated with 177Lu PSMA in eight high-volume European centers. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Baseline characteristics and clinical parameters during and after 177Lu PSMA treatment were documented. Correlations to treatment response were analyzed using χ2 and log-rank tests, with differences between groups with and without disease progression calculated using a Mann-Whitney U test. Univariate and multivariate-adjusted hazard ratios (HRs) were measured using Cox proportional hazards models. RESULTS AND LIMITATIONS: A prostate-specific antigen (PSA) decrease of ≥30% was observed in 41.7%, 63.5%, and 77.8% of patients after the first, second, and third treatment cycle, respectively. Restaging performed via PSMA positron emission tomography-computed tomography revealed that 33.7% of patients had an imaging-based response, including two patients with a complete response, while 13.4% had stable disease. The median time to progression was 5 mo and the median time until the start of a consecutive antineoplastic therapy was 8.5 mo. Of importance, a PSA decrease ≥30% after the first two cycles of 177Lu PSMA (1 cycle: p = 0.0003; 2 cycles: p = 0.004), absolute PSA after the first three cycles (1 cycle: p = 0.011; 2 cycles: p = 0.0005; 3 cycles: p = 0.002), and a PSA doubling time >6 mo (p = 0.009) were significantly correlated to treatment response. Furthermore, gamma-glutamyl transferase ≤31 U/L at the start of 177Lu PSMA therapy was correlated with 1.5 times higher risk of progression for patients without but not with visceral metastases (p = 0.046). CONCLUSIONS: 177Lu PSMA is an effective treatment option in mCRPC in the real-world setting. A PSA decrease ≥30% after the first two cycles is an early marker of response that can be easily implemented in clinical practice. PATIENT SUMMARY: 177Lu PSMA is a radioactive agent approved for treatment of advanced prostate cancer. We reviewed its use outside of clinical trials for patients treated at eight European centers. We found that 177Lu PSMA is an effective treatment option in real-world practice. A PSA (prostate-specific antigen) decrease of ≥30% after the first two therapy cycles is an early indicator of response to treatment and can be used in personalizing treatments for patients.
Keywords: výsledek terapie; radionuklidy; Neoplasm Metastasis; Male; retrospektivní studie; ligandy; Lutetium; antigeny povrchové; glutamátkarboxypeptidasa II; Ligands; Europe; Aged; Glutamate Carboxypeptidase II; mužské pohlaví; senioři; lutecium; Prostatic Neoplasms, Castration-Resistant; nádory prostaty rezistentní na kastraci; Treatment Outcome; Evropa; senioři nad 80 let; prostatický specifický antigen; lidé; Biomarkers, Tumor; Humans; Radioisotopes; Antigens, Surface; Aged, 80 and over; Retrospective Studies; metastázy nádorů; lidé středního věku; nádorové biomarkery; Prostate-Specific Antigen; Middle Aged